Pesan Tabligh dalam Buku 250 Wisdoms - Busyra, Muhammad (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2014)
Explores the communication of Islamic values through written media as a form of dakwah bil-qalam. The advancement of printing and digital technology has transformed human ways of thinking and communicating, including in delivering religious messages. Komaruddin Hidayat’s 250 Wisdoms presents a series of reflective aphorisms that express moral and spiritual teachings (amar ma’ruf nahi munkar) in a simple yet profound manner. This research aims to identify the macro structure (themes) and micro structure (semantic meaning) of the tabligh messages within the text. Using Van Dijk’s discourse analysis model and a qualitative approach, the study applies textual interpretation and literature review. The findings reveal that 250 Wisdoms conveys tabligh messages both explicitly and implicitly through syntactic, stylistic, and rhetorical structures. The study concludes that the book serves as an effective medium of Islamic propagation, delivering messages that are reflective, communicative, and humanistic bridging spiritual teachings with the realities of modern life.